Bariatrik cerrahi öncesi uygulanan proteinden zengin diyetin ağırlık kaybına, klinik sonuçlara ve karaciğer yağlanması üzerine etkisi - Özelgün, Demet (İstanbul Medipol Üniversitesi Sağlık Bilimleri Enstitüsü, 2017)
Bu çalışmada, bariatrik cerrahi ameliyatı geçirecek hastalara ameliyat öncesinde uygulanacak düşük kalorili, proteinden zengin diyetin antropometrik ölçümlere, klinik sonuçlara ve karaciğer yağlanması üzerine olan etkinliğinin araştırılması amaçlanmıştır. Bu araştırma, İstanbul Üniversitesi Cerrahpaşa Tıp Fakültesi ve Ankara Numune Eğitim ve Araştırma Hastanesi Genel Cerrahi Ana Bilim Dalı'nda yapılmıştır. Araştırmaya 18-65 yaş arası gönüllü otuz morbid obez hasta alınmıştır. Ameliyat öncesi (preop) on beş gün süreyle, on beş hastaya düşük kalorili proteinden zengin diyet (DKPZD), on beş hastaya ise Akdeniz Diyeti (AD) uygulanmıştır. Hastaların demografik bilgileri, tıbbi öyküleri, biyokimyasal bulguları, antropometrik ölçümleri, beslenme ve uyku kaliteleri değerlendirilip hasta izleme formuna kaydedilmiştir. Verilerin değerlendirilmesinde SPSS 22.0 programı kullanılmıştır. Çalışmamızda, her iki diyet öncesinde hastaların ağırlıkları 125,3 - 135 kg ve BKİ'leri 47,8 - 49,7 kg/m2 olarak saptanmıştır. Uygulanan DKPZD sonrasında 7,3 ± 2,3 kg, AD sonrasında ise 3,4 ± 0,8 kg ağırlık kaybı olduğu belirlenlenmiştir. Beden Kütle İndeksi (BKİ) DKPZD grubunda 2,8 ± 0,8 birim azalırken, AD grubunda ise 1,3 ± 0,3 birim azaldığı hesaplanmıştır (p ? 0.05). Her iki diyet grubunda total kolesterol, LDL ve HDL değerlerinde istatistiksel olarak anlamlı düşüşler saptanmıştır (p ? 0.05). Karaciğer boyutunda, DKPZD grubunda %5,5 düşüş görülmüştür (p ? 0.05). Çalışmamızın sonucunda, bariatrik cerrahi ameliyatı geçirecek hastaların preop dönemde düşük kalorili, proteinden zengin diyet ile ameliyata hazırlanması gerektiği kanısına varılmıştır.

The effectiveness of low caloric- high protein diet (LCHPD) on the anthropometric measurements, clinical results and liver fattening is to be aimed in this study. This study had been performed in Cerrahpasa Medicine Faculty and General Surgery Department of Ankara Training and Research Hospital. 30 morbid obese patients who are volunteers aged 18-65 had been included to this study. The low caloric- high protein diet had been performed on 15 of these patients as well as the Mediterranean Diet (MD) had been applied to the rest of the patients. The demographic information, medical records, biochemical results, anthropometric measurements and the quality of nutrition and sleep of these patients had been evaluated and recored to the patients inspection form respectively. The assessment of data had been performed by SPSS 22.0. In the both studies, the mean value of patients' weight was 125,3-135 kg while Body Mass Index (BMI) was 47,8 - 49,7 kg/m2 before starting LCHPD and MD programs. The mean weight loss had been observed 7,3 ± 2,3 kg for the patients receiving LCHPD program and 3,4 ± 0,8 kg for the patients receiving MD program. Also, the value of BMI in the group of patients who had been put LCHPD has decreased 2,8 ± 0,8 kg/m2 while1,3 ± 0,3 kg/m2 decrease had been observed in the patients receiving. On the other hand, 2,8 ± 0,8kg/m2 decrease in BMI for the patient group performed LCHPD and 1,3 ± 0,3kg/m2 decrease in BMI had been observed in the patient group taking MD have been determined (p ? 0.05). A statistically meaningful decrease in the blood levels of total cholesterol, LDL and HDL had been detected in the both diet groups (p ? 0.05). As a results, 5,5% liver size reduction had been observed in the patient group receiving LCHPD (p ? 0.05). A meaningful reduction in the liver size and decrease in the levels of blood lipids and anthropometric measurements had been observed in the results of the patients taking 2-week LCHPD program. However, the same positive results had not been observed in the MD patient group. Therefore, in the preoperative period of bariatric surgery patients, their diet should be determined/prescribed as a low caloric-high protein diet consideringly the remained time to the surgery.
The effects of protein-riched diet, performed before the bariatric surgery, on losing weight, clinical results and liver fattening
Keywords: Bariatrik Cerrahi; Preop Beslenme; Proteinden Zengin Diyet; Diyetisyen; Karaciğer Yağlanması; Bariatric Surgery; Preoperative Nutrition; High Protein Diet; Dietician; Liver Fattening